Historical and Spatial Development of City of Graz Park (Block 21), Pula, Croatia - Iva Rechner Dika; Alan Braun; Marin Duić (Prostor, 2025)
The article analyses the historical and spatial transformation of Block 21 in Pula, currently occupied by the City of Graz Park. The aim is to trace the site's development from antiquity to the present day and examine the layered changes in its urban and landscape structure. The methodology combines the analysis of historical maps, archival documents, conservation and urban planning studies, as well as field research. Particular attention is given to the impact of World War II destruction, the post-war landscape concept by architect Zdenko Kolacio, and subsequent planning documents. The research shows that while the area has retained ecological value, its spatial structure and historical legibility have significantly changed. The findings contribute to a deeper understanding of the area’s urban development and provide a basis for further study of its urban, architectural and archaeological context.